Comparative Analysis of School-Based Practical in Electrical and Electronics Trade Programme of Technical Colleges in Ogun State - Efuwape , Michael B.; Yisa , Abiodun M. (African Journal of Education,Science and Technology (AJEST), 2020)
This study investigated school-based practical in electrical and electronics trade programme of technical colleges in Ogun State. The study adopted a descriptive survey design. A sample of 105 respondents comprising 7 teachers and 98 year III students in electrical and electronics trade programme of two randomly selected technical colleges in Ogun State participated in the study. A structured Practical in Electrical and Electronics Trade Questionnaire validated by three experts was used for data collection in the study. A Cronbach Alpha reliability coefficient of 0.87 was obtained in a trial-test of the instrument in establishing its internal consistency. Three hypotheses guided the study. Data collected were analyzed using t-test at 0.05 level of significance. The findings revealed no significant difference in the mean responses of teachers and students from school I (df = 54; t = 2.755; p ˃ 0.05) and school II (df = 47; t = 1.541; p ˃ 0.05) on the extent to which practical activities hold in the training programme. On school-based practical activities, the study found no significant difference in the responses of respondents from the two schools (df = 103; t = 2.079; p ˃ 0.05). Based on the findings, it was recommended that school-based practical activities should be well monitored with focus on checking the standard of practical activities and compliance with industrial standards in order to improve quality of the training and production of well-equipped electrical and electronics trade graduates. It was also recommended that technical teachers should be encouraged to focus on relevant practical activities in electrical and electronics trade programme to avoid waste of time on irrelevant activities.